2016
DOI: 10.1097/bpb.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

MRI versus computed tomography as an imaging modality for postreduction assessment of irreducible hips in developmental dysplasia of the hip: an interobserver and intraobserver reliability study

Abstract: Following surgical reduction of an irreducible hip in developmental dysplasia of the hip, imaging is required to ascertain successful reduction. Recent studies have compared MRI versus computed tomography (CT) in terms of cost, time, sensitivity and specificity. This is the first study to compare intraobserver and interobserver reliability for both modalities. Nineteen CT scans of 38 hips in 10 patients and nine MRI scans of 18 hips in six patients were reviewed on two separate occasions by three clinicians. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…MRI has gained popularity over post-reduction CT scans due to its increasing availability and minimization of patients’ exposure to ionizing radiation. 2,22,23 Post-reduction MRI has the additional benefit of improved soft tissue and cartilage analysis. Potentially, the role of post-reduction MRI could be expanded beyond the dichotomous assessment of acceptable versus non-acceptable reduction, incorporating measurements of the femoral head position and acetabular morphology, which may have long-term implications for joint development.…”
Section: Discussionmentioning
confidence: 99%
“…MRI has gained popularity over post-reduction CT scans due to its increasing availability and minimization of patients’ exposure to ionizing radiation. 2,22,23 Post-reduction MRI has the additional benefit of improved soft tissue and cartilage analysis. Potentially, the role of post-reduction MRI could be expanded beyond the dichotomous assessment of acceptable versus non-acceptable reduction, incorporating measurements of the femoral head position and acetabular morphology, which may have long-term implications for joint development.…”
Section: Discussionmentioning
confidence: 99%
“…At present, some studies have suggested that MRI should be used as an imaging method for routine examination after conservative treatment of DDH [28,30], and some improvements have been made. For example, Fukuda et al [31] proposed using a 1.0-s ultrafast MRI without the need for anesthesia, and Barkatali et al [12] suggested that MRI could be performed with the child still sedated after manual reduction. Moreover, Dibello et al [32] and Jadhav et al [33] proposed MRI with fewer sequences [32][33][34], which meant that only the hip joint needed to be scanned to reduce examination time.…”
Section: Discussionmentioning
confidence: 99%
“…[31] proposed using a 1.0-s ultrafast MRI without the need for anesthesia, and Barkatali et al . [12] suggested that MRI could be performed with the child still sedated after manual reduction. Moreover, Dibello et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging examination, an important basis for early diagnosis, treatment, and follow-up after intervention of DDH, can directly reflect the hip structure and development of children [19][20][21][22]. Since DDH mostly occurs in infants and young children, the subjects for examination are special.…”
Section: Discussionmentioning
confidence: 99%